Respuesta :

[tex](-1, 9), \ (0, 6), \ (1, 4), \ (2, 2\frac{2}{3} ), \ (1, \frac{7}{9} )[/tex]

Solution:

Given [tex]f(x)=6\left(\frac{2}{3}\right)^{x}[/tex]

Domain = {–1, 0, 1, 2, 3}

Substitute the given values in the function.

At x = –1,

[tex]f(-1)=6\left(\frac{2}{3}\right)^{-1}[/tex]

         [tex]=6 \times \frac{3}{2}[/tex]

         = 9

[tex](x, f(x))=(-1, 9)[/tex]

At x = –0,

[tex]f(0)=6\left(\frac{2}{3}\right)^{0}=6[/tex]

[tex](x, f(x))=(0,6)[/tex]

At x = 1,

[tex]f(1)=6\left(\frac{2}{3}\right)^{1}=4[/tex]

[tex](x, f(x))=(1,4)[/tex]

At x = 2,

[tex]f(2)=6\left(\frac{2}{3}\right)^{2}[/tex]

       [tex]=\frac{24}{9}[/tex]

      [tex]=2\frac{6}{9}[/tex] (Cancel the common terms)

      [tex]=2\frac{2}{3}[/tex]

[tex](x, f(x))=(2, 2\frac{2}{3} )[/tex]

At x = 3,

[tex]f(3)=6\left(\frac{2}{3}\right)^{3}[/tex]

       [tex]=\frac{48}{27}[/tex] (Cancel the common terms)

       [tex]=\frac{16}{9}[/tex]

      [tex]=1\frac{7}{9}[/tex]

[tex](x, f(x))=(3, 1\frac{7}{9} )[/tex]

Plot the points in the graph.

The image of the graph is attached below.

Ver imagen shilpa85475
ACCESS MORE